Seed germination ecology of purple-leaf button weed (Borreria ocymoides) and Indian heliotrope (Heliotropium indicum): two common weeds of rain-fed rice - Chauhan, Bhagirath S.; Johnson, David E. (Cambridge University Press, 2008)
Purple-leaf button weed and Indian heliotrope are widespread and common weed species of rain-fed rice in many tropical countries. The influence of various environmental factors on seed germination of these species was studied. Seeds of both species germinated at a range of alternating temperatures (25/15, 30/20, and 35/25 C day/night). Germination of purple-leaf button weed was similar among light conditions after an after-ripening period of 3 mo, whereas germination of Indian heliotrope was always greater in light. Seed germination of both species was not affected by a high level of salt and a range of pH between 5 and 9, but was sensitive to high degrees of water stress. Seed burial strongly inhibited germination and emergence of these species. Seedling emergence of purple-leaf button weed (82 to 86%) and Indian heliotrope (70%) was optimal when seeds were sown in the top 0.2-cm soil layer. A burial depth of 2 cm completely inhibited emergence of Indian heliotrope, whereas, for purple-leaf button weed, this depth was 5 cm. Most of these seeds germinated, however, when brought to the soil surface. The information gained from this study would help in predicting the potential of these species for spreading into new areas, and could contribute to their control.